Road Traffic Accident: Motivation for Motorcycle Accident Prevention in Adolescents and Youth - Sridet , Rutshaporn; Phimphanchaiyaboon , Lunchana; Meesomsak, Nisapichayapak (Journal of Nursing, Siam University, 2022)
This academic article presenting the situations, causes, and factors related to the road accidents caused by motorcycles bring about the losses of adolescent and youth people. The main causes of this accident which is analyzed using the concept of The Protection Motivation Theory of Roger are as follows: the personal factors, the vehicle factors, and the environmental factors. Creating an impulse to raise awareness of the risks, perceived the severity of accidents, and the creation of incentives are suggested to prepare to meet the expectations for the safe riding of motorcycles effectively. The article also presents the methods and activities that are consistent with the concept of The Protection Motivation Theory as a guideline for interested people to use appropriately